PENGARUH KONFLIK GAM-RI DI BIDANG POLITIK DAN SOSIAL TERHADAP KEHIDUPAN MASYARAKAT ACEH TAHUN 1976-2012 - Eriyen Hertiana; Kian Amboro (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The problem faced in this research is how the influence of GAM-RI conflict is politically and socially on the lives of the people of Aceh especially in 1976-2012.The purpose of this study is to describe how the GAM-RI conflict, as well as explaining the influence of Aceh community in political and social fields. While this study is a historical study. In this study, using the methods of literary study. Data collection techniques in this study using the steps that heuristic and literature study. In testing the correctness of the data or the validity of data collection used internal and external criticism, while for the method of data analysis is the interpretation and historiography. Based on the research activities have been implemented, the effect of GAM-RI conflict in 1976-2012 in the field of politics is the enactment of the Military Operations Area and Military Emergency in Aceh as well as the emergence of Local Political Parties in Aceh. While the influence of the social field is to start the collapse of traditional values and norms that exist in Aceh and the change in attitude due to the impact felt by the people of Aceh conflict.